Atrial structure, function and arrhythmogenesis in aged and frail mice - Jansen, Hailey J. (Sci Rep, 2017)
Atrial fibrillation (AF) is prevalent in aging populations; however not all individuals age at the same rate. Instead, individuals of the same chronological age can vary in health status from fit to frail. Our objective was to determine the impacts of age and frailty on atrial function and arrhythmogenesis in mice using a frailty index (FI). Aged mice were more frail and demonstrated longer lasting AF compared to young mice. Consistent with this, aged mice showed longer P wave duration and PR intervals; however, both parameters showed substantial variability suggesting differences in health status among mice of similar chronological age. In agreement with this, P wave duration and PR interval were highly correlated with FI score. High resolution optical mapping of the atria demonstrated reduced conduction velocity and action potential duration in aged hearts that were also graded by FI score. Furthermore, aged mice had increased interstitial fibrosis along with changes in regulators of extracellular matrix remodelling, which also correlated with frailty. These experiments demonstrate that aging results in changes in atrial structure and function that create a substrate for atrial arrhythmias. Importantly, these changes were heterogeneous due to differences in health status, which could be identified using an FI.